PATH-05. A RETROSPECTIVE STUDY OF TREATMENT STRATEGIES AND OUTCOMES IN WHO GRADE II AND III ISOCITRATE DEHYDROGENASE (IDH) WILD-TYPE ASTROCYTOMA. (9th November 2020) - Aaroe, Ashley; Dono, Antonio; Youssef, Michael; Alfaro-Munoz, Kristin; Weathers, Shiao-Pei; O'Brien, Barbara; Majd, Nazanin; Harrison, Rebecca; Loghin, Monica; Soomro, Zaid; Williford, Garret; Fuller, Gregory; et al.
Abstract: BACKGROUND: WHO grade II and III IDH wild-type astrocytomas behave more aggressively than their IDH mutated counterparts. A subpopulation shares molecular features with the novel entity proposed in cIMPACT-NOW Update 3 "Diffuse astrocytic glioma, IDH wild-type, with molecular features of glioblastoma (GBM), WHO IV". METHODS: We performed a retrospective analysis of clinical and molecular features, management and survival of 134 adult patients treated for grade II and III IDH wild-type astrocytoma between 06/2012 and 12/2018 at MD Anderson Cancer Center (MDACC - 112) and UT Health Science Center at Houston (UTHSC - 22). All patients had IDH1 sequenced, all but 2 had IDH2 sequenced, and 73 had further next generation sequencing. RESULTS: Median age at diagnosis was 53 (interquartile range 18-83). 82 patients (61%) were male. 31 patients were histologically diagnosed with grade II astrocytoma, 102 with grade III astrocytoma, and one with diffuse glioma (insufficient tissue to render histologic grade or perform sequencing). EGFR alterations were found in 31 patients and TERT promoter mutations in 22. 84 (63%) received concurrent chemoradiation and adjuvant temozolomide (grade II, n=9; grade III, n=74; NOS, n=1). PFS overall was 12.0 months (grade II = 17.9; grade III = 10.7). OS in patients treated with concurrent chemoradiation and adjuvant temozolomide was 17.1 months versus 17.7 in patients treated with sequential radiation and temozolomide (p = NS), and 10.6 in patients treated with RT alone or surveillance (p< 0.016). The highest 2-year OS was seen in grade II patients treated with concurrent chemoradiation and adjuvant temozolomide (60%). CONCLUSIONS: WHO grade II and III IDHwt astrocytoma survival is similar to historical GBM cohorts. The proportion meeting molecular criteria for GBM is yet undefined. Groups who received chemotherapy may perform better than those who do not. Further analysis of MGMT methylation and other molecular factors is ongoing.